Out-of-Class Activities Employed by Successful and Unsuccessful English Department Students - Cayandrawati Sutiono; Ali Saukah; Suharmanto Suharmanto; Monica D.D. Oka (Pascasarjana UM, 2017)
Abstract: This study aims at exploring the out-of-class activities employed by the successful and unsuccessful students of the English Department. The activities involve out-of-class general activities and out-of-class English learning activities. The general activities are categorized into academic activities, social activities, leisure activities, and part-time jobs, while the English learning activities are Self-In-struction, Naturalistic Language Learning and Self-Directed Naturalistic Language Learning. This study is qualitative in nature. It was done through (1) documents analysis, (2) in-depth interviews done one by one with the participants.Key Words: out-of-class activities, out-of-class general activities, out-of-class English learning activities, successful students, unsuccessful studentsAbstrak: Penelitian ini bertujuan untuk menelusuri aktivitas pembelajaran di luar kelas yang dilakukan oleh mahasiswa Jurusan Bahasa Inggris yang sukses dan tidak sukses. Aktivitas tersebut terdiri dari aktivitas umum dan aktivitas pembelajaran Bahasa Inggris. Pada aktivitas umum terdiri dari aktivitas akademis, aktivitas sosial, aktivitas santai, dan pekerjaan paruh waktu, sedangkan aktivitas pembelajaran Bahasa Inggris adalah pembelajaran diri, Pembelajaran Bahasa Naturalistik, dan Pembelajaran Bahasa Naturalistik Acu Diri. Penelitian ini merupakan penelitian dengan rancangan kualitatif. Penelitian ini dilakukan melalui (1) analisis dokumen, (2) wawancara mendalam satu persatu dengan responden.Kata kunci: pembelajaran di luar kelas, aktivitas umum, aktivitas pembelajaran bahasa inggris, mahasiswa yang sukses, mahasiswa yang tidak sukses